2018
DOI: 10.1186/s12913-018-3405-2
|View full text |Cite
|
Sign up to set email alerts
|

Simulation-based low-dose, high-frequency plus mobile mentoring versus traditional group-based training approaches on day of birth care among maternal and newborn healthcare providers in Ebonyi and Kogi States, Nigeria; a randomized controlled trial

Abstract: BackgroundThere is limited information from low and middle-income countries on learning outcomes, provider satisfaction and cost-effectiveness on the day of birth care among maternal and newborn health workers trained using onsite simulation-based low-dose high frequency (LDHF) plus mentoring approach compared to the commonly employed offsite traditional group-based training (TRAD). The LDHF approach uses in-service learning updates to deliver information based on local needs during short, structured, onsite, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
19
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
3
2

Relationship

4
1

Authors

Journals

citations
Cited by 7 publications
(28 citation statements)
references
References 12 publications
(13 reference statements)
2
19
0
Order By: Relevance
“…Our findings are consistent with those of previous studies that reported that TRAD offsite training may improve the trainees' competencies, but knowledge and skills may not be transferred to other co-workers at the facility, nor translated into practice or performance [13][14]. On the other hand, methods that involve repetitive, mentor-supported learning and regularly coordinated practice sessions, such as the onsite LDHF/m-mentoring training, resulted in better skills acquisition and retention over time [1,[7][8][11][12][13][14][15][16][17].…”
Section: Discussionsupporting
confidence: 87%
See 2 more Smart Citations
“…Our findings are consistent with those of previous studies that reported that TRAD offsite training may improve the trainees' competencies, but knowledge and skills may not be transferred to other co-workers at the facility, nor translated into practice or performance [13][14]. On the other hand, methods that involve repetitive, mentor-supported learning and regularly coordinated practice sessions, such as the onsite LDHF/m-mentoring training, resulted in better skills acquisition and retention over time [1,[7][8][11][12][13][14][15][16][17].…”
Section: Discussionsupporting
confidence: 87%
“…The authors have attempted a brief description of the methodology. The training approaches, eligibility criteria and randomization have been described in the published study protocol [11].…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Nigeria, with a population of 185.7 million as of 2017 (according to Nigeria Bureau of Statistics), has six geopolitical zones and 36 states plus the Federal Capital Territory (FCT). The study was conducted in two states: Ebonyi state has a population of 2.8 million and is in the South-East zone; Kogi state has a population of 4.3 million and is in the North-Central zone [5]. At the time of the study, the…”
Section: Study Settingmentioning
confidence: 99%
“…There are few studies from low-and middle-income countries (LMICs) on learning outcomes and facilitators and barriers to learning approaches on day-of-birth care among maternal and newborn health workers trained using onsite simulation-based low-dose, high-frequency (LDHF) plus mobile (m)-mentoring training approach compared to those trained by offsite traditional group-based training (TRAD). The LDHF/m-mentoring approach is described in the study protocol manuscript; it differ from the TRAD approach primarily by being onsite, more interactive, and team-oriented thus more suited to meet the needs of the trainees in various contextual situations [5]. The LDHF/m-mentoring approach also uses mobile phone mentorship calls and reminder text messages to the trainees.…”
Section: Introductionmentioning
confidence: 99%